Archaeological expedition to al khashbah (2023): Rock art survey - Döpper, Stephanie (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
In 2023, a new project on rock art in Eastern Arabia, with special focus on the Al Sharqiyah North Governorate started. It aims at recording the spatial and chronological distribution of rock art as well as its integration into the natural and anthropogenic landscape. In the first field season from February to April 2023, over 4,000 rock art images have been recorded at the sites of Al Tasawir, Lizq, Al Khashbah and Al Rakhi. This encompassed digital sketches of the rock art panels, photography of the individual rock art images, taking of UTM coordinates, and vectorising the photographs on a computer later on. In addition, 3D models of all recorded sites were generated by structure-from-motion (SfM). As a citizen science component of the project, a smartphone application (Rock Art Oman) was developed that allows everyone to support the project by documenting rock art in an easy manner. This does not only provide more data for research but also help to foster the awareness of people in Oman for their rock art heritage.
Keywords: Archéologie -- Oman

Life Histories of Mudbrick Settlements in Central Oman - Döpper, Stephanie; Biezeveld, Irini (Mudbrick Settlements of the Oman Peninsula Inhabited - Abandoned - Re(dis)covered, 2025)
Keywords: Architecture -- Oman; Archéologie -- Oman; Urbanisme -- Oman

The production of Bahlā Ware in the context of late Islamic Oman - Živković, Jelena; Lopez, Jose Carvajal; Döpper, Stephanie; Biezeveld, Irini (Proceedings of the Seminar for Arabian Studies, 2025)
Among glazed Arabian Gulf wares, Bahlā Ware stands out as one of the most documented objects of consumption at sites in Oman, the UAE, Qatar, and Bahrain from the sixteenth to the early twentieth century. Previous scientific studies of Bahlā Ware from UAE and Qatar formed the basis for understanding its production technology and provenance, as well as the unique composition of its lead-barium glaze. This paper presents the new results of petrographic and chemical analyses of thirty-two Bahlā samples from Oman, contributing to a better understanding of the compositional variability of ceramics, the provenance of raw materials, and techniques used for the application of lead-barium glazes. The compositional match between samples of Bahlā Ware from Oman, the UAE, and Qatar reveals the exploitation of the same geological source of raw materials over several centuries. Previous research has associated this source with the ophiolitic geological formation in Oman. The results of chemical analysis of glazes confirmed that the Omani samples were also coated with a lead-barium glaze of the same type as reported for UAE and Qatar.
Keywords: Archéologie -- Oman; Céramique -- Oman

Mudbrick Settlements of the Oman Peninsula Inhabited - Abandoned - Re(dis)covered - Döpper, Stephanie; Mershen, Birgit; Kanditt, Josephine; Biezeveld, Irini; Schmidt-Lux, Thomas (Sidestone Press, 2025)
Caught between the poles of remembering and forgetting, glorification and neglect, the abandoned mudbrick settlements (ḥārāt) of Oman are a vital object of conflicting processes of interpretation and negotiation. Adopting a diachronic perspective, the multi-disciplinary book’s chapters examine their past, present and future. The book presents approaches and results of archaeological, ethnographic, historical and sociological research on abandoned ḥārāt. Oman’s landscape is dotted with abandoned mudbrick settlements and quarters, known as ḥārāt, either isolated in the countryside or surrounded by vibrant, modern urban centres. Most of them were abandoned during the economic upturn and opening of the country after Sultan Qaboos bin Said came to power in 1970. People’s move from traditional mudbrick to modern concrete houses led to the deterioration and decay of the physical substance of the mudbrick buildings. In the face of these conditions, various Omani and international actors have repeatedly warned against the uncontrolled loss of this valuable cultural heritage. The former inhabitants of the mudbrick houses and their descendants have also repeatedly emphasised their emotional attachment to these abandoned places and their personal significance to them. At the same time, others, especially tourists, have glorified the dilapidated state of the ruins as an aesthetically beautiful backdrop for a romanticised vision of the past. This was the starting point for the interdisciplinary research project “The abandoned mudbrick settlements of central Oman: Between romanticisation and neglect”, funded by the Gerda Henkel Foundation as part of the “Lost Cities” programme between 2020 and 2022, and conducted by the editors of the present volume. It constitutes the proceedings of the closing conference of the project, in which team members present their results and leading experts give their input on inhabited, abandoned and re(dis)covered mudbrick settlements in the Sultanate of Oman.
Keywords: Architecture -- Oman; Archéologie -- Oman; Urbanisme -- Oman

Reclaimed, Rediscovered or Reinvented – The Changing Perceptions of Ḥārāt since the Omani Nahḍa - Mershen, Birgit (Mudbrick Settlements of the Oman Peninsula Inhabited - Abandoned - Re(dis)covered, 2025)
Keywords: Architecture -- Oman; Archéologie -- Oman; Urbanisme -- Oman

Modern Architectures vs ‘Pre-Modern’ Ḥārāt: Architecture Against the Tribes in Oman - Delitz, Heike (Mudbrick Settlements of the Oman Peninsula Inhabited - Abandoned - Re(dis)covered, 2025)
Keywords: Architecture -- Oman; Archéologie -- Oman; Urbanisme -- Oman

#Mudbrick #Oman: On the Tourist Perception of Abandoned Ḥārāt Architecture - Kanditt, Josephine; Schmidt-Lux, Thomas (Mudbrick Settlements of the Oman Peninsula Inhabited - Abandoned - Re(dis)covered, 2025)
Keywords: Architecture -- Oman; Archéologie -- Oman; Tourisme -- Oman; Urbanisme -- Oman

Documentation of Omani Traditional Settlements (Ḥārāt): Reality and Aspirations - Mahrooqi, Ali Bin Hamood al- (Mudbrick Settlements of the Oman Peninsula Inhabited - Abandoned - Re(dis)covered, 2025)
Keywords: Architecture -- Oman; Archéologie -- Oman; Urbanisme -- Oman

Harat Al ʿAqr in Nizwa and Three Artistic Traditions - Bandyopadhyay, Soumyen; Briguglio, Claudia (Mudbrick Settlements of the Oman Peninsula Inhabited - Abandoned - Re(dis)covered, 2025)
Keywords: Architecture -- Oman; Archéologie -- Oman; Urbanisme -- Oman

Memory and Belonging in the Bat Oasis, Oman - Young, Ruth; Brooks, Alasdair (Mudbrick Settlements of the Oman Peninsula Inhabited - Abandoned - Re(dis)covered, 2025)
Keywords: Architecture -- Oman; Archéologie -- Oman; Urbanisme -- Oman